1994
DOI: 10.1016/0925-8388(94)90951-2
|View full text |Cite
|
Sign up to set email alerts
|

Atomic thermal vibrations of the light actinide elements

Abstract: We have been using time-of-flightneutron powder diffractionto determine the Debye-Waller factorsof the lightactinideelements. The Debye-Wallerfactor isa measure of the mean-squareatomicdisplacementthatarisesfromthe thermalmotionof the atomsin any solid. Its temperaturedependencedeterminesa Debye-Wallertemperature,®DW,that is characteristic of the elasticpropertiesof the solid.The data are obtainedby Rietveld

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Diffraction measurements on a-U at ambient pressure have shown that the Debye temperature decreases dramatically with increasing temperature [3,16]. This softening is consistent with decreases in the elastic constants [17,18].…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Diffraction measurements on a-U at ambient pressure have shown that the Debye temperature decreases dramatically with increasing temperature [3,16]. This softening is consistent with decreases in the elastic constants [17,18].…”
supporting
confidence: 49%
“…Independently, there has been recent interest in the vibrational entropy contribution to the high temperature phase stability of metals and alloys [9][10][11], motivated by the discovery that vibrational entropy plays a larger role in phase stability than previously expected [12]. Other experimental and theoretical work has shown that electronic contributions to the entropies of high temperature phase transitions can also be significant [13][14][15].Diffraction measurements on a-U at ambient pressure have shown that the Debye temperature decreases dramatically with increasing temperature [3,16]. This softening is consistent with decreases in the elastic constants [17,18].…”
mentioning
confidence: 99%
“…Robert (Non-spin-polarized) 103 Robert (Spin-polarized AFM) 103 Kutepov (NM) 104 Kutepov (AFM) 104 Söderlind (SO) 38 Söderlind (SO+OP) 38 Kay (ultrasonic resonance) 87 our result (RUS) 20 (x-ray 12 , dilatometry [105][106][107][108] 169. 103 Robert (Spin-polarized AFM I) 103 Robert (Spin-polarized AFM II) 103 Söderlind (SO) 38 Söderlind (SO+OP) 38 Kay ( Robert (Non-spin-polarized) 103 Robert (Spin-polarized AFM) 103 Kutepov (NM) 104 Kutepov (AFM) 104 Shick (LSDA) 109 Shick (FLL LSDA+U) 109 Shick (AMF LSDA+U) 109 Söderlind (SO) 38 Söderlind (SO+OP) 38 Söderlind (EMTO) 38 Kay ( which summarizes the best previous thermal expansion and x-ray measurements of pure Pu.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The errors in the fitted Θ DW s are less than 1K for β-through ε-phases and about 10K for α. (See Lawson et al, 1994, for details of the fitting process.) There is nothing in the <u 2 > curve that correlates with the negative thermal expansion of the δ-phase.…”
Section: Electron Correlation and Plutonium Phase Diagramsmentioning
confidence: 99%